Educational Perspective: The Exploration of Learning Methods in Kung Fu Panda 1 - Triana, Audia; Imaniah, Ikhfi; Hanim, Imtihan (Institut Agama Islam Negeri Palopo, 2025)
In the world of education, there are still some educators who have not implemented learning methods according to learning needs. This is due to the lack of teacher knowledge about teaching and learning techniques. The study aims to provide a reference for learning methods for teachers in the hope that educational goals will be achieved properly. This study uses the Kung Fu Panda film as a research object to analyze its learning methods so that it can be used as a reference or source for teachers out there. This study uses qualitative research design and content analysis techniques to describe messages or information in film clips that are relevant to the methods in the Kung Fu panda film, namely Interest-based learning, Demonstration learning, Drill learning, and Experiential learning. All methods are used to shape the character of Po and his other students into wise and intelligent people. The results of the study show that the techniques applied are in accordance with the main goal of education, namely guiding students to become knowledgeable, skilled, and characterful people. Keywords: Education Perspective, Learning Method, Kung Fu Panda